What Justifies a Future with Humans in It?. (26th September 2016) - Murphy, Timothy F.
Abstract: Antinatalist commentators recommend that humanity bring itself to a close, on the theory that pain and suffering override the value of any possible life. Other commentators do not require the voluntary extinction of human beings, but they defend that outcome if people were to choose against having children. Against such views, Richard Kraut has defended a general moral obligation to people the future with human beings until the workings of the universe render such efforts impossible. Kraut advances this view on the grounds that we are obliged to exercise beneficence toward others and on the grounds that the goods available in human lives are morally compelling. This account ultimately succeeds in making no more than a prima facie defense of human perpetuation because considerations of beneficence could override – in some cases probably should – override any duty to perpetuate human beings. While the goods of human life may be distinctive, they cannot serve as reason‐giving in regard to their own perpetuation. Ironically, the exercise of beneficence may authorize the extinction of human beings, if it becomes possible to enhance the goods available to human descendants in a way that moves them away from human nature as now given. The defense of a morally obligatory and strictly human future remains elusive, even as it becomes morally desirable to work against Fateful Catastrophes, those human‐caused events that threaten to extinguish existing lives already good and enriching for their bearers.